Сlinical features of asthma-COPD overlap syndrome with comorbid type 2 diabetes mellitus - V.O. Halytska; H.Ya. Stupnytska (Mìžnarodnij Endokrinologìčnij Žurnal, 2023)
Background. Comorbidity profiles are a common subject of research in patients with asthma-COPD (chronic obstructive pulmonary disease) overlap (ACO), but in case of concurrent type 2 diabetes mellitus (T2DM), there is a lack of targeted research on the quality of life, clinical course, and lung function. The aim of the study was to clarify the clinical features of asthma-COPD overlap in combination with T2DM. Materials and methods. Sixty-nine patients were examined: 24 with ACO and T2DM (group 1), 21 with asthma and T2DM (group 2), and 24 with COPD and T2DM (group 3). A diagnosis of ACO was made according to GINA and GOLD 2017 guidelines. Quality of life was assessed using the CAT, ACQ, and SGRQ, and the severity of dyspnea was assessed using the mMRC scale, disease severity and prognosis using the BODE index. Spirometry with bronchodilation test, 6-minute walk test, and bioimpedance analysis were performed. Results. Patients in the main group had a higher total SGRQ score than those in group 3 (by 33 %, p = 0.001). Higher ACQ and total SGRQ scores indicate a trend toward worse asthma control and lower quality of life in patients with ACO and T2DM compared to the asthma + T2DM group (p = 0.056 and p = 0.054, respectively). Body mass index was higher than in patients with COPD and T2DM (by 16.3 %, p = 0.001). Higher serum glucose levels were found in patients with ACO and T2DM than in those with COPD and T2DM (by 18.3 %, p = 0.028). The FEV1 in the ACO and T2DM group was lower than in the asthma + T2DM group (by 18.7 %, p = 0.027), and the SVC was lower by 33 % (p = 0.021). There was a tendency to a lower result in the 6-minute walk test in the main group compared to patients from group 3 (p = 0.0548), and a higher frequency of exacerbations per year compared to groups 2 (p = 0.08) and 3 (p = 0.06). Conclusions. Patients with asthma-COPD overlap and concurrent type 2 diabetes mellitus have worse quality of life, lower FEV1 and SVC, submaximal exercise tolerance, higher fasting glucose levels, and a tendency towards increased exacerbation frequency.